2004
DOI: 10.1161/01.cir.0000148955.19792.8d
|View full text |Cite|
|
Sign up to set email alerts
|

Arterial Biology for the Investigation of the Treatment Effects of Reducing Cholesterol (ARBITER) 2

Abstract: Background— Niacin reduces coronary heart disease morbidity and mortality when taken either alone or in combination with statins; however, the incremental impact of adding niacin to background statin therapy is unknown. Methods and Results— This was a double-blind randomized placebo-controlled study of once-daily extended-release niacin (1000 mg) added to background statin therapy in 167 patients (mean age 67 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
197
2
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 836 publications
(207 citation statements)
references
References 33 publications
2
197
2
6
Order By: Relevance
“…Of note, far-wall CIMT and its changes have been associated with cardiovascular risk and used to measure response to therapy in clinical trials. 3,16 Because there were fewer participants at the high end of the CIMT range, greater differences between the techniques for high or extreme CIMT values cannot be excluded. Incorporation of a BDP into an inexpensive lightweight or portable ultrasound system, validation of an abbreviated scanning protocol for officebased cardiovascular risk assessment, and studies demonstrating improved cardiovascular outcomes using CIMT measurements are needed to continue to facilitate clinical use of CIMT measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, far-wall CIMT and its changes have been associated with cardiovascular risk and used to measure response to therapy in clinical trials. 3,16 Because there were fewer participants at the high end of the CIMT range, greater differences between the techniques for high or extreme CIMT values cannot be excluded. Incorporation of a BDP into an inexpensive lightweight or portable ultrasound system, validation of an abbreviated scanning protocol for officebased cardiovascular risk assessment, and studies demonstrating improved cardiovascular outcomes using CIMT measurements are needed to continue to facilitate clinical use of CIMT measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, for offline readings, images are acquired and stored on videotape or a digital medium and read at a later moment in time [7]. This offline reading approach is most often used in clinical trials, using either semi-automated edge detection programs [8][9][10] or manual edge detection of the ultrasound interfaces [11][12][13][14]. Semi-automated edge detection is more often applied in settings in which only the common carotid artery is examined, whereas manual edge detection is usually applied in those settings in which the maximum CIMT of multiple carotid segments is measured.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have provided data on the reproducibility, risk factor relations and rates of change in common CIMT using automated or manual edge detection [8][9][10][11][12][13][14]. However, comparison of results from these studies to compare reading methods is useless, because differences could be explained by many other factors such as differences in study population or scanning procedures rather than by differences in reading method alone.…”
mentioning
confidence: 99%
“…58 Despite the negative findings of recent large-scale trials, several earlier studies -though at smaller scales -have reported an opposite finding. 18,33,[59][60][61][62][63][64] A recent meta-analysis also favored the benefits of niacin either as monotherapy or as an adjunct to statins in reducing CVD events. 64 It is also worth noting that both AIM-HIGH and HPS2-THRIVE studies were secondary prevention trials in subjects receiving optimal statin therapy.…”
Section: Discussionmentioning
confidence: 99%